(untitled) (CIPEEX, 2025)
Skin assessment is a fundamental step in the physical examination in aesthetics, providing crucial data for therapeutic planning. The objective of this study was to highlight the importance of structured skin assessment for ensuring the safety and effectiveness of aesthetic treatments, allowing the identification of alterations that may impact clinical outcomes. A narrative literature review was carried out using national and international scientific sources, with searches conducted in databases such as SciELO, LILACS, and PubMed between 2023 and 2025. The research focused on inspection and palpation methods, in addition to non-invasive technologies for detailed evaluation. The results indicated that structured skin assessment, through manual methods and technology, enables the identification of biophysical parameters such as hydration, elasticity, and texture, as well as dyschromias and other inflammatory processes. Collecting these data supports the development of individualized therapeutic plans, prevents risks, and qualifies aesthetic planning, ensuring a personalized and safe approach. In conclusion, skin assessment is an indispensable stage of the physical examination in aesthetics, and its systematic and detailed performance ensures both the safety and efficacy of procedures. Furthermore, it strengthens ethical and evidence-based professional practice, positively impacting patient satisfaction and health. The differences observed among age groups demonstrate the importance of documenting specific care and treatments tailored to each age range.